Aspects of the pathogenicity and immunological relations of the one rabies virus atrain isolated from Desmodus rotundus rotundus bat - Silva, Renato Augusto da (Pesquisa Agropecuaria Brasileira, 2014)
A strain of rabies virus was isolated from vampire bat, Desmodus rotundus rotundus, captured in the Country of Blumenau State of Santa Catarina (South of Brazil). The characteristics of pathogenicity were studied in the mice and bovines. The immunological relations with standard rabies virus (Pasteur, strain), were studied by neutralization and cross-imunization tests. This strain was for us designated IPEACS 1.661 and in the present time contains forty-three passages in the mice, retained some of its street virus properties with Negri bodies formation into nervous cells and multiplication in the salivar glands of inoculated bovines by intra-muscular route.